The influence of Corporate Governance,Capital Structure, and Profitability on Company Value: Pengaruh Tata Kelola Perusahaan, Struktur Modal, dan Profitabilitas terhadap Nilai Perusahaan - Leony Patracia; Ibram Pinondang Dalimunthe (Academia Open, 2026)
General Background: Firm value represents a critical indicator of corporate performance and investor perception in capital markets, particularly in sectors providing essential goods where demand remains relatively stable. Specific Background: The consumer non-cyclical sector in Indonesia demonstrated resilience during the 2019–2023 period despite economic disruption caused by the COVID-19 pandemic and subsequent recovery dynamics. Knowledge Gap: Previous studies report inconsistent findings regarding the relationships between corporate governance, capital structure, profitability, and firm value, while limited empirical research specifically examines these relationships in the consumer non-cyclical sector during the post-pandemic period. Aims: This study investigates the relationships between corporate governance, capital structure, and profitability with firm value in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2019–2023. Results: Using panel data regression with a Random Effect Model on 69 companies and 345 observations, the findings show that capital structure measured by the Debt to Equity Ratio has a significant relationship with firm value measured by Price to Book Value, whereas corporate governance measured by the ASEAN Corporate Governance Scorecard and profitability measured by Return on Assets show no significant relationship individually. However, the variables jointly form a statistically significant regression model. Novelty: The study contributes empirical evidence from the post-COVID-19 economic recovery period with a sector-specific focus on consumer non-cyclical firms, highlighting how financing policies signal market valuation dynamics. Implications: These findings indicate that financing decisions and debt management remain key considerations for investors in assessing firm prospects, while corporate governance implementation and profitability indicators require deeper substantive alignment with business strategy to support long-term corporate valuation. Highlights • Capital structure represented by Debt to Equity Ratio shows a significant relationship with firm valuation.• Governance score and asset-based profitability display insignificant individual relationships with market valuation indicators.• Post-pandemic analysis of 69 Indonesian consumer staple companies reveals financing policy as a dominant market signal. Keywords Corporate Governance; Capital Structure; Profitability; Firm Value; Consumer Noncyclical Sector